2002
DOI: 10.1080/00071660120121526
|View full text |Cite
|
Sign up to set email alerts
|

Response of broiler chicks to dietary Rhazya stricta and Nigella sativa

Abstract: 1. Rhazya stricta leaves and Nigella sativa seeds were fed to 7-d-old Hibro broiler chicks at 20 and 100 g/kg of the diet for 7 weeks. Although 20 and 100 g/kg N. sativa seed diets did not adversely affect growth, a decrease in body weight and feed efficiency and hepatonephropathy were observed in the chicks fed on the 100 g/kg R. stricta diet. 2. These changes, associated with macrocytic hypochromic anaemia, were correlated with alterations in serum aspartate transaminase' (AST) and alanine transaminase (ALT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 5 publications
2
33
0
7
Order By: Relevance
“…In this respect, Gilani et al (2004) and Amad and Radman (2013) suggested that as feed supplement acts as stimulator for the digestive system activity and promotes the appetite and palatability. Similar results were obtained by Al-Homidan et al (2002) who reported improved feed intake by incorporating black cumin seeds in broiler rations. Moreover, Azeem et al (2014) demonstrated a significant increase in feed consumption in broilers fed NSM up to 10% which could be due to the different ways of affecting body metabolism by NSM.…”
Section: Sbm Reached 40% (Corresponding To 16% Of Nsm)supporting
confidence: 79%
“…In this respect, Gilani et al (2004) and Amad and Radman (2013) suggested that as feed supplement acts as stimulator for the digestive system activity and promotes the appetite and palatability. Similar results were obtained by Al-Homidan et al (2002) who reported improved feed intake by incorporating black cumin seeds in broiler rations. Moreover, Azeem et al (2014) demonstrated a significant increase in feed consumption in broilers fed NSM up to 10% which could be due to the different ways of affecting body metabolism by NSM.…”
Section: Sbm Reached 40% (Corresponding To 16% Of Nsm)supporting
confidence: 79%
“…NS and its various extracts were found to possess antibacterial activity against gram positive and gram-negative bacteria, and they caused inhibition of aflatoxin production (Nasir and Grashorn, 2006). Application of NS seeds has shown some effects on broilers performance (Al-Homidan et al, 2002;Guler et al, 2006;Durani et al, 2007;Ziad et al, 2008), layer performance and egg quality (Akhtar et al, 2003;Nasir et al, 2005). But, the findings of these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of NS contain alkaloids, fixed and volatile oils and a variety of pharmacologically active substances like thymoquinone, dithymoquinone, thymol, carvacrol, nigellicine-N-oxide, nigellidine and alpha-hedrin (Al-Homidan et al, 2002;Nasir et al, 2005). NS and its various extracts were found to possess antibacterial activity against gram positive and gram-negative bacteria, and they caused inhibition of aflatoxin production (Nasir and Grashorn, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bu yasağın ardından antibiyotiklere alternatif olarak kullanılabilecek büyümeyi uyarıcı çeşitli organik maddeler üzerinde yapılan çalışmalar daha da hız kazanmıştır. Bu bağlamda üzerinde durulan maddelerden birisi de aromatik bir bitki olan çörek otu tohumu [3][4][5][6][7][8] ve bundan elde edilen yağlardır [9][10][11][12] .…”
Section: Introductionunclassified
“…Broyler rasyonlarına %2 ve 10 oranında çörek otu tohumu ilave edilerek yapılan bir başka çalışmada [3] , çörek otu ilave edilen gruplardaki hayvanların canlı ağırlık artışı kontrol grubundan önemli derecede yüksek bulunmuştur. Aynı çalışmada, çörek otu verilen grupların yem tüketimi ve yemden yararlanma oranı kontrol grubundan rakamsal olarak daha yüksek bulunmuştur.…”
Section: Introductionunclassified